2002
DOI: 10.1128/mcb.22.19.6788-6796.2002
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Targeting by the Growth Factor Midkine

Abstract: Ligand-receptor internalization has been traditionally regarded as part of the cellular desensitization system. Low-density lipoprotein receptor-related protein (LRP) is a large endocytosis receptor with a diverse array of ligands. We recently showed that LRP binds heparin-binding growth factor midkine. Here we demonstrate that LRP mediates nuclear targeting by midkine and that the nuclear targeting is biologically important. Exogenous midkine reached the nucleus, where intact midkine was detected, within 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
129
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 74 publications
2
129
0
4
Order By: Relevance
“…As nucleolin does not have a hydrophobic domain for its anchorage in the plasma membrane, LRP could be the nucleolin partner that allows surface expression of nucleolin and thus its proper functioning. This is in accord with the data of Shibata et al [24] who have reported that both LRP and nucleolin are necessary for MK endocytosis. However, in our experiment MK becomes concentrated in the cytoplasm and does not enter the nucleus, whereas in the experiments of Shibata et al, the internalized MK is translocated to the nucleus.…”
Section: Internalization Of Mk By An Active Process Is Inhibited By Tsupporting
confidence: 93%
“…As nucleolin does not have a hydrophobic domain for its anchorage in the plasma membrane, LRP could be the nucleolin partner that allows surface expression of nucleolin and thus its proper functioning. This is in accord with the data of Shibata et al [24] who have reported that both LRP and nucleolin are necessary for MK endocytosis. However, in our experiment MK becomes concentrated in the cytoplasm and does not enter the nucleus, whereas in the experiments of Shibata et al, the internalized MK is translocated to the nucleus.…”
Section: Internalization Of Mk By An Active Process Is Inhibited By Tsupporting
confidence: 93%
“…All-trans-retinoic acid as well as 13-cis-retinoic acid induced the intracellular production of MK, but did not enhance the secretion of MK, probably because of premature binding, as described below (manuscript in preparation). The endocytosis of MK is completely dependent on LRP, and initiates nuclear targeting by MK, which is partly needed for the antiapoptotic activity of MK (Shibata et al, 2002). In addition, LRP functions as a biosynthesis regulator for MK.…”
Section: Discussionmentioning
confidence: 99%
“…The downstream signaling systems of these receptors include ERK, which participates in the reduction of necrotic and apoptotic cell death [21] . Internalization of midkine in to cell and nuclear targeting is important for its antiapoptotic function [22] . Activation of these receptors and intracellular pathways might take part in cytoprotective effects of midkine during Cd toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that midkine is beneficial for liver regeneration [29] . ERK, JNK signal pathways disturbed during Cd toxicity are activated by midkine [18,19,22,30] . Beneficial effects of exogenous midkine to minimize Cd induced damage would provide a new perspective for innovation in the treatment of Cd intoxications and in NonAlcoholic Fatty Liver Disease (disease near exclusively characterized by apoptotic process), in Drug Induced Liver Injury and in the combined form, illnesses far long more evident than Cd intoxication in the every day practice of gastroenterologists and hospitals.…”
Section: Discussionmentioning
confidence: 99%